Penentuan Tebal Bahan Transparan (ZnO) Menggunakan Interferometer Michelson - Edy Nugroho, Sulung; Firdausi, K. Sofjan; Marhaendrajaya, Indras (BERKALA FISIKA, 2007)
Thickness’ determination of ZnO material on a substrate (microscope slide) by using Michelson Interferometer has been carried out. The material used in the research was ZnO transparent material deposited on a 1 mm-thickness of a microscope slide. Refractive index of the microscope slide and the thickness of ZnO were measured by counting the fringes transitions as the materials rotated large as , on the other words, fringes transitions as function of sinus incident angles of laser ray, . Incident angles of laser ray, which are used in the measurement of ZnO transparent material thickness on microscope slide, are 1°, 2°, 3°, 4°, 5°, 6°, 7°, 8°, 9°, and 10°. Laser ray used in this research was He-Ne laser, which has 633 nm and its output power was < 1 mW. The results of this research show that there were fringes transitions as research-materials rotated large as . The measured fringes transitions still have remarkable agreement with the theoretical fringes transitions. As the incident angles increases, the fringes transitions will increase as well as. The thickness of the ZnO thin film, which is resulted from the research, is equal to (6.0 ± 1.8) × 10-5 m.